Grammatical Competence in EFL Learners: A Quantitative Study on the Misuse of 'To Be' at University Level - Magvirah Octasary; Nahdawati Nahdawati; Indry Widyasti Anwar (Hasanuddin University, 2025)
Developing grammatical competence is crucial to mastering the English language because it enables learners to construct precise and meaningful sentences in both written and spoken contexts. The verb to be is one of the most significant grammatical elements since it can serve as a primary verb, an auxiliary verb, or a copula. However, EFL learners frequently struggle to use it appropriately, which frequently leads to errors in sentence construction, tense formation, and subject-verb agreement. Both their general language acquisition development and their academic writing abilities may suffer as a result of these persistent problems. In light of these issues, this study investigates the grammatical competence of university-level EFL (English as a Foreign Language) learners, focusing specifically on the misuse of the verb to be. The research employs a quantitative approach involving grammar tests and written analysis from fourth semester of English education students of Sekolah Tinggi Keguruan dan Ilmu Pendidikan Abdul Mujib Laewang Dampal Selatan. Results reveal frequent errors in subject–verb agreement, tense usage, and sentence structure, with misformation and omission being the most common error types. The findings suggest a need for more targeted grammar instruction and continuous practice in academic writing.